2017
DOI: 10.3847/2041-8213/836/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

13CO/C18O Gradients across the Disks of Nearby Spiral Galaxies

Abstract: We use the IRAM Large Program EMPIRE and new high-resolution ALMA data to measure 13 CO(1-0)/C 18 O(1-0) intensity ratios across nine nearby spiral galaxies. These isotopologues of 12 CO are typically optically thin across most of the area in galaxy disks, and this ratio allows us to gauge their relative abundance due to chemistry or stellar nucleosynthesis effects. Resolved 13 CO/C 18 O gradients across normal galaxies have been rare due to the faintness of these lines. We find a mean 13 CO/C 18 O ratio of 6.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
8
40
0
Order By: Relevance
“…In all these cases, the low ratios have been attributed to the presence of massive stars in a recent starburst. Our trends found for L ( 13 CO )/L (C 18 O) ( Figure 10) are in good agreement to previous ratios reported for starburst galaxies (Zhang et al 2018;Jiménez-Donaire et al 2017). Considering the 24 VALES galaxies with C 18 O spectral coverage, we show moderate trends of L ( 13 CO )/L (C 18 O) with L IR , SFR, and SFE.…”
Section: Co)supporting
confidence: 91%
“…In all these cases, the low ratios have been attributed to the presence of massive stars in a recent starburst. Our trends found for L ( 13 CO )/L (C 18 O) ( Figure 10) are in good agreement to previous ratios reported for starburst galaxies (Zhang et al 2018;Jiménez-Donaire et al 2017). Considering the 24 VALES galaxies with C 18 O spectral coverage, we show moderate trends of L ( 13 CO )/L (C 18 O) with L IR , SFR, and SFE.…”
Section: Co)supporting
confidence: 91%
“…They typically range from 2.2 (for the entire bar) to 4.4 (for the center). This result falls within the range of the values for other local spiral galaxies (e.g., Jiménez-Donaire et al 2017).…”
Section: Regionally Averaged Quantities In Each Galactic Structuresupporting
confidence: 85%
“…This process can enhance the abundance of 13 CO by a factor of ∼2-3 at low temperature and low optical depth in molecular clouds (Szűcs et al 2014). It is believed to have a non-dominant effect on large (kpc) scales in the discs of galaxies (Paglione et al 2001), though our C 18 O(1-0) observations do not rule out fractionation as an important effect (Jiménez-Donaire et al 2017c). The lowest ℜ ratios are found in the centres of a few galaxies and ℜ anti-correlates with dust temperature and Σ SFR for those galaxies, the inverse of what is expected from chemical fractionation.…”
Section: The ℜ Ratio: Origin Of Variationsmentioning
confidence: 65%
“…Simulating a suite of molecular clouds, Szűcs et al (2014) showed that the effect of selective photo-dissociation on the 12 CO/ 13 CO abundance ratio is minimal. Jiménez-Donaire et al (2017c) also argue that shielding from dust and H 2 dominates over self-shielding of CO molecules. Therefore, we do not consider selective photo-dissociation as a dominant effect.…”
Section: The ℜ Ratio: Origin Of Variationsmentioning
confidence: 94%